Soluble expression, rapid purification, biological identification of chicken interferon-alpha using a thioredoxin fusion system in E. coli and its antiviral effects to H9N2 avian influenza virus. Issue 2 (7th February 2019) - Zhao, Jun; Yu, Hai-Yang; Zhao, Yu; Li, Feng-Hua; Zhou, Wei; Xia, Bin-Bin; He, Zhi-Yuan; Chen, Jason; Jiang, Guo-Tuo; Wang, Ming-Li
Abstract: In this paper, we report a soluble expression based on Escherichia coli and two-step purification of a novel thioredoxin-tagged chicken interferon-α fusion protein (Trx-rChIFN-α) by using pET32a(+) expression system. The mature ChIFN-α gene was amplified by Reverse transcriptase-polymerase chain reaction (RT-PCR) and subcloned into pET-32a (+) vector prior to transformation into Rosetta (DE3) competent cells. After IPTG induction, the recombinant fusion protein was expressed efficiently in the soluble fraction. The protein purification was performed by nickel affinity chromatography and DEAE anion exchange chromatography. The purified product has a purity of 95% with a yield of 47.3 mg/L of culture. The specific activity of the fusion protein reaches to 2.0 × 10 7 IU/mg as determined in the CEF/VSV titration system. After excision of the Trx tag by enterokinase, the remaining solo protein was confirmed as rChIFN-α protein by SDS-PAGE, N-terminal sequencing and mass spectrometry. The effects of this Trx-rChIFN-α fusion protein against H9N2 influenza virus infection were also evaluated in ovo . The results showed that the Trx-rChIFN-α protein could significantly reduce the hemagglutination titer of H9N2 virus, and the H9N2 viruses HA gene copy numbers. These findings will enable us to produce large amount and bio-active rChIFN-α protein for future applications.